THE DIFFERENCE OF PAIN PERCEPTION BETWEEN KETOPROFEN SUPPOSITORY AND 1% PERIPROSTATIC LIDOCAINE INJECTION - Azis, Abdul; Djatisoesanto, Wahjoe; Soebadi, Doddy M.; Hakim, Lukman; Budiono, Budiono (Indonesian Urological Association, 2012)
Objective: To compare the pain control results of ketoprofen suppository and periprostatic injection of lidocaine 1% for prostate biopsy. Material & Method: A total of 30 patients who underwent transrectal ultrasound guided prostate biopsy were randomized into 2 groups. Group 1 consisted of 15 patients received 200 mg of ketoprofen suppository. Group 2 received 1% periprostatic lidocaine injection. A visual analog scale was used to assess the pain score during prostate biopsy. Statistical analysis of pain scores was performed using independent t-test and Pearson correlation test. Results: The 2 groups were homogenous in age and prostate volume. There was significant difference in pain score among groups 1 and 2 during prostate biopsy (mean VAS ± SD 0,8 ± 0,8 and 4,5 ± 1,6 respectively, p < 0,0001). There was no significant correlation between pain perception with age (p = 0,779), or prostate volume (p = 0,389) in both groups. Conclusion: Periprostatic lidocaine injection is more effective for decreasing the pain for prostate biopsy compared to ketoprofen suppository. Keywords: Prostate biopsy, pain, transrectal ultrasonography, periprostatic nerve block, visual analog scale.